REKONFIRMASI POSISI PANCASILA VIS-A-VIS ISLAM - Suratno, - (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2008)
After the fall of Suharto regime in May 1998, political change wasnot only marked by the more democratic political atmosphere, butalso by the awakening of radical and conservative Islam groups.These groups have ample rooms to promote their agenda.Although they have different agendas such as the implementationof Islamic law, the establishment of Islamic state and even ofIslamic Caliphate in Indonesia, they are similar in their attempts toreplace Pancasila as the state foundation into Islam. This articleaims to show that these attempts are not enough rooted in thehistory. Historically, the founding fathers clearly stated thatIndonesia is neither an Islamic nor secular state; it is a state foundedon Pancasila. This phrase summarizes the difficult compromisesand agreements among the founding fathers of this Republicconcerning the official national ideology, i.e., between the Islamistand nationalist groups. It brings us to a few months before and afterthe independence day declared on August 17, 1945. There shouldbe no contradiction between Pancasila and Islam. ModerateMuslims in Indonesia already have enough reason to reject the ideaof an Islamic state as well as to accept Pancasila as a political reality,as the common platform for a plural Indonesia.